2019
DOI: 10.1097/md.0000000000014361
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nutritional status by dual X-Ray absorptiometry in women with rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) has been related to an impairment of the nutritional status. Body mass index (BMI) has been used but questions arise about how to properly evaluate nutritional status in RA patients. Few studies have evaluated it by dual-energy X-ray absorptiometry. In women with RA, to analyze: their nutritional status compared to that of a control population, differences between the prevalence of impairment of nutritional status measured by dual energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
(24 reference statements)
2
15
0
Order By: Relevance
“…Another study by Reina, demonstrated that RA patients fulfilled criteria of sarcopenia in 44% of cases versus 19% of controls (100 subjects); moreover, this study demonstrated that RA disability is inversely correlated to lean mass and directly to fat trunk; also, that RA time of evolution correlates inversely with lean mass in limbs and SMI: more long and aggressive disease provokes a loss of muscle mass [43].…”
Section: Energy Intake Body Mass Index (Bmi) Body Composition Physical Activity and Rheumatoid Arthritissupporting
confidence: 49%
“…Another study by Reina, demonstrated that RA patients fulfilled criteria of sarcopenia in 44% of cases versus 19% of controls (100 subjects); moreover, this study demonstrated that RA disability is inversely correlated to lean mass and directly to fat trunk; also, that RA time of evolution correlates inversely with lean mass in limbs and SMI: more long and aggressive disease provokes a loss of muscle mass [43].…”
Section: Energy Intake Body Mass Index (Bmi) Body Composition Physical Activity and Rheumatoid Arthritissupporting
confidence: 49%
“…Both the disease and medication might affect body composition. In particular, glucocorticosteroids increase appetite and influence body composition by increasing WC and reducing muscle mass [ 42 ]. Since obesity is associated with higher disease activity, lower probability of remission, and poorer treatment response to medication, management of obesity is of utmost importance [ 25 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although body mass index (BMI) has been associated with sarcopenia in previous publications [28][29][30][31][32], many studies show that muscle mass loss is not always associated with lower BMI. The low or no weight loss in these patients is explained by a stable or slightly increased fat mass, i.e., sarcopenic obesity.…”
Section: Nutritional Statusmentioning
confidence: 99%